2010
DOI: 10.1539/joh.l10057
|View full text |Cite
|
Sign up to set email alerts
|

Work and Family Stress is Associated with Menstrual Disorders but not with Fibrocystic Changes: Cross‐sectional Findings in Chinese Working Women

Abstract: Work and Family Stress is Associated with Menstrual Disorders but not with FibrocysticChanges: Cross-sectional Findings in Chinese Working Women: Mei ZHOU, et al. School of Public Health, Kunming Medical University, ChinaObjectives: To explore the separate and combined effects of work and family stress on menstrual disorders and fibrocystic changes in Chinese working women. Methods: Data were obtained from a cross-sectional study of 1,642 female railway workers. The EffortReward Imbalance Questionnaire and Fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 36 publications
2
26
1
3
Order By: Relevance
“…As several of these conditions are included in the ERI model, application of this model to the Chinese working population has been well justified 11) . Our previous research in China has identified effort-reward imbalance at work as one significant risk of cardiovascular diseases 12,13) , musculoskeletal disorders 14) , reproductive hazards 15) , mental distress 16) , impaired health functioning 17) , and professional turnover 18) . The original ERI questionnaire is based on 23 items 19) .…”
mentioning
confidence: 99%
“…As several of these conditions are included in the ERI model, application of this model to the Chinese working population has been well justified 11) . Our previous research in China has identified effort-reward imbalance at work as one significant risk of cardiovascular diseases 12,13) , musculoskeletal disorders 14) , reproductive hazards 15) , mental distress 16) , impaired health functioning 17) , and professional turnover 18) . The original ERI questionnaire is based on 23 items 19) .…”
mentioning
confidence: 99%
“…Ketegangan tersebut membuat pekerja memberikan tanggapan yang melebihi kemampuan penyesuaian terhadap stressor di tempat kerja (Harianto, 2008 Sebuah penelitian yang dilakukan pada pekerja wanita di Tiongkok tahun 2010 menyebutkan bahwa, sebanyak 59,3% karyawan mengalami gangguan menstruasi yang berhunbungan dengan stres kerja (Zhou, 2010 …”
Section: Pendahuluanunclassified
“…Penelttian sebelumnya oleh Mulastin (2011) pada pekerja wanita di Desa Palemkerep Jepara menghasilkan kesimpulan bahwa ada hubungan secara bermaknaantara stress kerja dengan menstruasi (α= 0,05, ρ= 0,00). Zhou (2010) dalam penelitiannya pada pekerja wanita di Tiongkok juga menyimpulkan bahwa ada hubungan antara stres kerja dengan menstruasi (α= 0,05, ρ= 0,01).…”
Section: Sumber: Data Primer Penelitianunclassified
“…Accordingly, China offers a special case for this research, compared with their spouses, Chinese mothers play the primary role of homemakers; at the same time they are additionally exposed to pressure from work [24], [25]. This combined workload has been shown to increase the burden of Chinese women's work-related disease [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…A psychometrically validated questionnaire measuring effort–reward imbalance at work in Chinese language has been developed [31]. Following the predictive utility of this measure in previous epidemiologic studies in China [27], [32], we included a test of this model in the present study.…”
Section: Introductionmentioning
confidence: 99%